Design of Frequency Reconfigurable Antenna Working in Ka Band - Siddhanth Sahu, N; Mohith, B; Nikhil, G; Ch. Sri Kavya, K; K. Kotamraju, Sarat (International Journal of Engineering and Technology, 2018)
In this study of reconfigurable antenna technology is presented. The important applications that can be used with the reconfiguring techniques, studying the history of this technology in brief literature survey is examined. A detailed information on the technique background information are specified, reviewing the different reconfigurable components, which can be used in an antenna to adjust its functionality and construction. These reconfigurable antenna techniques are divided with a different classification method and explain whichever established on the physical changes of the reconfigurable antenna radiating parts, or on the integration of varactors, photoconductive components, PIN diodes, or on the function of materials etc. the designed covers the Fixed-Satellite (space-to-Earth), Mobile satellite 19.7GHz to 20.2GHz applications.Â